Analogija med strukturama države in mednarodne skupnosti - Šabič, Zlatko (Teorija in praksa, 2011)
The aim of this article is to analyse the role of diplomacy in the changing environment of international relations caused by globalisation and alterations to the global world order. In doing so, the author uses a model of an analogy between the structure of the state and the structure of the international community. In his analysis, he focuses on those actors which participate in global governance and best fit the so-called "domestic analogy": international governmental and non-governmental organisations, and international parliamentary institutions. He argues that, as the nature of problems which an individual faces becomes more global, decision-making processes will increasingly also take place at the global level. The more global governance becomes "government" the more pressure by non-state actors to participate in these processes will mount. In such an environment, traditional diplomacy is becoming a means of communication used not only by states but also by other actors.
Keywords: Governance; Vladanje; Mednarodne organizacije; International organizations; Diplomacija; Diplomacy; mednarodna skupnost; nevladne organizacije; state; država